Novel nanocomposites and nanoceramics based on polymer nanofibers using electrospinning process—A review - Chronakis, Ioannis S. (Journal of materials processing technology, 2005)
Electrospinning is a very simple and versatile process by which polymer nanofibers with diameters ranging from a few nanometers to several micrometers (usually between 50 and 500 nm) can be produced using an electrostatically driven jet of polymer solution (or polymer melt). Significant progress has been made in this process throughout the past few years and the resultant nanostructures have been exploited to a wide range of applications. This review covers the active research area of producing ceramic and composite nanofibers with various compositions and properties by means of the electrospinning process. Current critical issues are discussed, such as carbon nanofibers made from electrospun precursor polymer nanofibers, encapsulation and alignment of carbon nanotubes within nanofibers to construct unique functional composite nanostructures, and organic–inorganic nanofibers (hybrids).